2014
DOI: 10.7860/jcdr/2014/8247.4835
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Mental Health: A Study of Work-Related Mental Health among Clinical Nurses

Abstract: Objective: This paper reports a study performed to investigate and assess the mental health as well as the demographic characteristics of nurses to examine their mental health status based on four physical, anxiety, social-function and depression items. Materials and Methods:This descriptive cross-sectional study was accomplished on 86 nurses working at three hospitals, affiliated to Iranian health ministry, in Ilam city(western Iran) all the cases were selected by purposeful sampling method.Data was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…The findings of the present study showed that 76.3% of frontline nurses were suspected of poor mental health; this rate was significantly higher in our study than in previous mental health surveys done on Iranian nurses under non-COVID-19 conditions (in the study by Dehvan et al, it was 57.35%, and in the study by Taghinejad et al, it was 43.2%) (23,24).…”
Section: Discussioncontrasting
confidence: 66%
“…The findings of the present study showed that 76.3% of frontline nurses were suspected of poor mental health; this rate was significantly higher in our study than in previous mental health surveys done on Iranian nurses under non-COVID-19 conditions (in the study by Dehvan et al, it was 57.35%, and in the study by Taghinejad et al, it was 43.2%) (23,24).…”
Section: Discussioncontrasting
confidence: 66%
“…According to the European Commission [6], some of these psychosocial risks are time pressure; rigid hierarchical structures; lack of gratification and reward; inadequate personnel leadership; lack of relevant information; lack of support from management staff; work-related loads (shift work, night work, irregular working hours); social conflicts, harassment, bullying, violence and discrimination: difficulties in the field of communication and interaction, including the failure to comprehend body language and, work organization which is not ideal (working-time arrangements). In this field, some studies indicated that there are high levels of psychological illness among healthcare workers [15][16][17][18][19]. In accordance, psychosocial and work factors that may contribute to this issue should be analysed in order to better explore healthcare workers wellbeing [20].…”
Section: Occupational Health and Well-beingmentioning
confidence: 99%
“…Hence, it has a great significance for managers of hospitals to pay special attention to the mental health of nurses (13). According to the statistics published by Iran's Nursing Council, 75% of nurses are suffering from some degrees of mental and physical diseases (14). According to epidemiological surveys, one-third of the population is affected by an anxiety disorder during its lifetime and therefore, anxiety is the most important problem in contemporary times (15).…”
Section: Introductionmentioning
confidence: 99%